A Supramolecular "Trident" for Cancer Immunotherapy. (31st March 2021) - Li, Xinxin; Wang, Yuhan; Zhang, Yiming; Liang, Chunhui; Zhang, Zhenghao; Chen, Yaoxia; Hu, Zhi‐Wen; Yang, Zhimou
Abstract: Immunotherapy has shown great promise for the treatment of cancer. However, the limited efficacy of single‐agent immunotherapy hinders its widespread application, which stimulated the investigation of combination therapy with improved efficacy. Herein, a tri‐functional immunostimulatory supramolecular nanomedicine consisting of indoximod (IND, an indoleamine 2, 3‐dioxygenase (IDO) inhibitor), D PPA‐1 (a D‐peptide antagonist against programmed cell death ligand‐1 (PD‐L1)), and a self‐assembling D‐tetrapeptide of G D F D F D Y (a powerful adjuvant with immunostimulatory properties) is reported. The resulting IND‐G D F D F D Y‐ D PPA‐1 behaves as a supramolecular "trident, " and its three functional parts play parallel roles to boost the effective immune responses. It is shown that the supramolecular "trident" exhibits a stronger binding ability to PD‐L1 than the D PPA‐1 peptide (>fourfold) and is able to inhibit the IDO‐1 pathway more efficiently than IND itself. The supramolecular "trident" activates and recruits the cytotoxic CD8 + T lymphocytes along with other immune effector cells in tumors, concomitant with downregulation of Foxp3 + T cells and upregulation of tumor immune‐related cytokines, thus showing a strong ability to improve the tumor microenvironment and enhance immunotherapeutic effects to prevent tumor growth and metastasis in the breast tumor model. The findings may stimulate the development of self‐assembling peptide‐based multifunctional nanomedicines for cancer therapy. Abstract : A tri‐functional immunostimulatory supramolecular nanomedicine, bearing the IDO inhibitor, PD‐L1 blockade, and assembling tetra‐peptide immune adjuvant is developed and applied for cancer immunotherapy. It significantly improves the tumor microenvironments and thus shows a superior capacity to inhibit tumor growth.